Clients' Perception and Satisfaction with Nursing Care During the Intra-Natal Period in a University Teaching Hospital, Nigeria - OYEDIRAN, OLUFEMI; OPARA, Rita Ogechi; ADENIRAN, Ganiyat; AFOLABI, Opeyemi O.; OYIBOCHA, Elizabeth O.; Ojo, Iyanuoluwa O.; AYANDIRAN, Emmauel O. (British Journal of Healthcare and Medical Research, 2022)
Every minute in a day, somewhere in the world, a woman dies due to complications arising from pregnancy and childbirth and Nigeria is not an exception with a very poor record regarding maternal and child health outcomes. This study determined clients’ perception and satisfaction with nursing care during the intra-natal period at Lagos State University Teaching Hospital, Lagos. A descriptive cross-sectional design was adopted for the study using a purposive sampling technique. A 60-item questionnaire was used to collect data from the 259 selected participants. Data were collated, processed, and analyzed with Statistical Package for Social Sciences (SPSS) version 25. Descriptive and inferential statistics were used to present data. Findings from the study revealed that 61.4% of respondents have positive perception towards nursing care during the intra-natal period, 48.3% of respondents were highly satisfied with the nursing care received during the intra-natal period and 84.9% of respondents identified the availability of equipment to provide care as a major factor that influences satisfaction with nursing services. There was a significant association between perception with nursing care and satisfaction with nursing care. {χ2= 22.11, df = 2, p=0.01}. The study concluded that availability of equipment to provide care, management of the ward, and nurses' interaction with family and staff were factors influencing satisfaction with nursing care. Hence, Nurses should improve their skills in nurses-patient relationship and hospital management also provide necessary equipment for better intra-natal care.